ANALISIS FAKTOR FUNDAMENTAL TERHADAP EXCESS RETURN SAHAM SYARIAH PERUSAHAAN JAKARTA ISLAMIC INDEX - Azwar Azwar; Indo Yama Nasarudin; Arief Mufraini; Suhendra Suhendra; Sihabudin Noor (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
The study concluded that based on the results of testing by using multiple regression analysis, there are four variables that significantly affect the excess return variables, they are: BV,DER, ROE and SWBI. Besides, they are other variables such as PER, nflation, and exchange rate had no significant effect on the variable excess stock returns. Thus, it can be assumed that the JII firms during the study period was fulfilling aspects of sharia compliance. The indications are book value can represent the real value of the assets of the company itself and the highest ratio of debt to asset is 2.84%. meanwhile, the highest determination of Islamic National Council is 33%DOI: 10.15408/aiq.v3i1.2501